Counting the Costs: A Method for Evaluating the Cost of Achieving SDG 11 - Prakash, Mihir; Kamiya, Marco; Ndugwa, Robert; Cheng, Mengfan (Frontiers in Sustainable Cities, 2020)
As we enter the decade of action on the SDGs, it is necessary to have quantifiable information on the relevant costs of achieving the Sustainable Development Goals (SDGs). Without this information, it will be difficult for decision-makers and stakeholders to effectively allocate existing and scarce resources as well as identify the resource gap that would need to be bridged through exploration and implementation of feasible alternate financing mechanisms. Several studies have estimated the global resource needs to achieve the SDGs, but none identify a clear way to estimate these costs for cities, which are expected to deliver on the SDG agenda for the anticipated 70% of the world's population by 2050. This is perhaps because resource needs vary significantly with city context. Acknowledging this need and to stimulate the dialogue on local costs of sustainability, this study proposes a novel method to determine the cost of achieving housing, transportation, public spaces and solid waste management dimensions (or hard costs) of Sustainable Development Goal 11 (SDG 11) as well as the cost of municipal governance and planning (soft costs) for cities in developing countries. The study also demonstrates the value proposition of using a systematic approach to model the costs of achieving SDG 11 by applying this method to four countries. Apart from sharing the proposed method, the study shares four key findings: (1) despite the inherent difficulty of quantifying and standardizing what comprehensive urban sustainability means for all cities, urban experts do agree on objective criteria of what a baseline level of urban performance should be for some of its dimensions; (2) pursuit of sustainable cities implies different things depending on the development status of the country; (3) cities of different sizes have differing needs and costing methods need to account for transitions from small- to medium-size and medium- to large-size over time; and (4) better understanding needs to be built of what achievement might look like in practice for the subjective targets of SDG 11 such as those pertaining to “heritage and conservation” and “disaster risk and resilience.”